Modified homotopy perturbation method for solving hypersingular integral equations of the first kind - Eshkuvatov Z.K.; Zulkarnain F.S.; Nik Long N.M.A.; Muminov Z. (SpringerOpen, 2024)
Indexed by WOS/ Scopus